1984
DOI: 10.1016/0191-815x(84)90045-7
|View full text |Cite
|
Sign up to set email alerts
|

High level waste immobilization forms

Abstract: ABSTRACT. Various solid HLW forms compared for leach resistance, irradiation stability, processing, and physical properties yield alkali borosilicate glass and titanate based ceramics as leading waste forms. Titanates offer the possibility of higher waste loading. Glass waste forms offer the advantage of simpler and demonstrated full-scale and radioactive remote processing operations. Predictions of glass-repository performance based upon leaching kinetics, solubility limits, thermodynamics, and multiple films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(37 citation statements)
references
References 61 publications
(98 reference statements)
0
37
0
Order By: Relevance
“…The calculation of dissolution rates of NZP structure has demonstrated that it would take 20 000 times longer to dissolve NZP than quartz [21]. Work has also been reported on 3 powder and then completely mixed. The mixture was dried, prepared by thermal treatment in the temperature range of 650-1200 ℃ for 5 h. They found that the Cs or Sr immobilized material is thermally and chemically resistant, and the excellent leaching resistance is attained at 700 ℃.…”
Section: Immobilization Of Hlw By Ceramicsmentioning
confidence: 93%
See 3 more Smart Citations
“…The calculation of dissolution rates of NZP structure has demonstrated that it would take 20 000 times longer to dissolve NZP than quartz [21]. Work has also been reported on 3 powder and then completely mixed. The mixture was dried, prepared by thermal treatment in the temperature range of 650-1200 ℃ for 5 h. They found that the Cs or Sr immobilized material is thermally and chemically resistant, and the excellent leaching resistance is attained at 700 ℃.…”
Section: Immobilization Of Hlw By Ceramicsmentioning
confidence: 93%
“…Waste loadings of between 60-65 wt% have been achieved for Synroc waste forms. This corresponds to a volumetric concentration of 2.3-2.5 g/cm 3 and an equivalent Curie content of about 1.0 Ci/cm 3 . The leaching test is carried out according to the MCC-1 [29].…”
Section: Immobilization Of Hlw By Ceramicsmentioning
confidence: 99%
See 2 more Smart Citations
“…At INEL, liquid HLW is calcined to a free-flowing granular solid (calcine) and stored in stainless-steel tanks. Most of these wastes will require incorporation into a stable, solid medium (e.g., glass) for final disposal (Hench 1984). "he total volume of HLW at the end of 1991 was 3.966 x 10 m , at a total radioactivity of 9.969 x 1 0 ' curies (Ci).…”
Section: Treating Hlw Is a Multistep Process (Gao 1993)mentioning
confidence: 99%